2016
DOI: 10.1021/acs.orglett.6b00372
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Allenamides by Copper-Catalyzed Coupling of Propargylic Bromides and Nitrogen Nucleophiles

Abstract: An efficient and general synthesis of allenamides derived from oxazolidinones and hydantoins is reported. Upon activation with a combination of a copper catalyst and a 2,2'-bipyridine derivative in the presence of an inorganic base, propargylic bromides were found to be suitable reagents for the direct allenylation of nitrogen nucleophiles by a formal copper-catalyzed S(N)2' reaction. Besides the availability of the starting materials, notable features of this route to allenamides are its mild reaction conditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…While each of these strategies has led to great success and was found to be compatible with many functional groups, an intrinsic drawback arises from the redox and step economy of these transformations (Scheme 1). [8a,d–e,9e,h,12] More precisely, in either case, the adjustment of the final oxidation state within the target molecule and the establishment of the desired skeletal connectivity takes place in more than one chemical operation. Against this background, a catalytic process that unifies an intermolecular C−N bond formation with the desired oxidation state in the target compound appears to be a strategically sound complement to the portfolio of classical protocols.…”
Section: Methodsmentioning
confidence: 99%
“…While each of these strategies has led to great success and was found to be compatible with many functional groups, an intrinsic drawback arises from the redox and step economy of these transformations (Scheme 1). [8a,d–e,9e,h,12] More precisely, in either case, the adjustment of the final oxidation state within the target molecule and the establishment of the desired skeletal connectivity takes place in more than one chemical operation. Against this background, a catalytic process that unifies an intermolecular C−N bond formation with the desired oxidation state in the target compound appears to be a strategically sound complement to the portfolio of classical protocols.…”
Section: Methodsmentioning
confidence: 99%
“…In the previous works from Kutal, [ 10 ] Mitani, [ 11 ] Sauvage, [ 12 ] Peters, Fu, [ 13 ] Reiser, [ 14 ] and others, copper complexes have exhibited unique property as cheaper photoredox catalyst, capable of activating a broad range of substrates including organic halides. [ 14,15 ]…”
Section: Background and Originality Contentmentioning
confidence: 99%
“…217, 218 Demmer et al recently reported the synthesis of N-1-allenyl-hydantoins by a copper-catalyzed coupling reaction involving propargylic bromides. 219 Hydantoin-containing macrocycles such as crown ethers 220 could be synthesized by double alkylation of phenytoin with oligo(ethylene glycol) diiodide. Macrocyclic bis-hydantoin structures could as well be obtained by metathesis of the allyl N-1 substituents of both hydantoin cores.…”
Section: Use Of 11-carbonyldiimidazole (Cdi)mentioning
confidence: 99%
“…Copper-catalyzed coupling reactions of allenyl or aryl iodides and hydantoins were reported, as well as ruthenium-catalyzed hydroamidation of alkynes. , Demmer et al recently reported the synthesis of N -1-allenyl-hydantoins by a copper-catalyzed coupling reaction involving propargylic bromides . Hydantoin-containing macrocycles such as crown ethers could be synthesized by double alkylation of phenytoin with oligo­(ethylene glycol) diiodide.…”
Section: 35- and 1355-substituted Hydantoinsmentioning
confidence: 99%